Turkish pre-service teachers’ understanding of daily life phenomena related to chemistry and compatibility with the current chemistry curriculum - AĞLARCI ÖZDEMİR, OYA (My University, 2023)
The aim of this study is to determine Turkish pre-service science teachers’ levels of chemical explanations of various daily life phenomena and to investigate whether these examples are in accordance with the high school chemistry curriculum in Turkey. This study was carried out with descriptive research methods. The participants are 71 freshmen pre-service science teachers in a state university in Turkey. The data of the study were collected with the \"Chemical Explanations of Daily Phenomena\" Questionnaire previously developed in the literature. The phenomena in the questionnaire were related to chemistry concepts such as diffusion, temperature, combustion reactions and the law of conservation of mass, isotopes, reaction rate, redox reactions, and mixtures and solutions. The answers were analyzed in three categories: correct, wrong, and can’t determine and the frequencies and percentages of the categories were determined. Also, the learning outcomes in the latest version of the Turkish high school chemistry curriculum were examined in order to determine whether they were related to the chemistry concepts in the questionnaire. Document analysis was utilized to analyze the learning outcomes in the chemistry curriculum. The findings of the study revealed that most of the pre-service teachers answered correctly the questions that are compatible with the chemistry curriculum. Their misconceptions were mostly related to heat transfer and specific heat capacity, the law of conservation of mass, and heavy water and isotopes. The findings indicated that future curriculum changes should integrate some important chemistry concepts closely related to everyday life, such as radioactivity and heat transfer.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Social Sciences and Humanities; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities